Synthesis and Antimicrobial Studies of Some New 3-Isoxazoline Substituted Phthalazine Methylsulfonyl Oxadiazoles - A. M. Sridhara; K. R. Venugopala Reddy; J. Keshavayya; D. S. Ambika; Sanathkumar Goud; S. K. Peethambar (E-Journal of Chemistry)
A series of new 3-isoxazoline substituted phthalazine methylsulfonyl-oxadiazoles were prepared from methyl 2-(4-oxo-3,4-dihydrophthalazin-1-yl) acetate. The structure of synthesized compounds were characterized by spectral data and screened for their antimicrobial activities against various bacteria and fungi strains. Several of these compounds showed antimicrobial activity.